2021
DOI: 10.1155/2021/8888712
|View full text |Cite
|
Sign up to set email alerts
|

Production of Poly(3-Hydroxybutyrate) by Haloarcula, Halorubrum, and Natrinema Haloarchaeal Genera Using Starch as a Carbon Source

Abstract: Microbial production of bioplastics, derived from poly(3-hydroxybutyrate) (PHB), have provided a promising alternative towards plastic pollution. Compared to other extremophiles, halophilic archaea are considered as cell factories for PHB production by using renewable, inexpensive carbon sources, thus decreasing the fermentation cost. This study is aimed at screening 33 halophilic archaea isolated from three enrichment cultures from Tunisian hypersaline lake, Chott El Jerid, using starch as the sole carbon sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Extremophilic microorganisms, particularly haloarchaea, show all the optimum features to be a good candidate to produce PHA on a large scale: Microbial growth can be achieved by using waste carbon sources and there is no need for medium sterilization, minimal risk of contamination by other microorganisms, use of brines or seawater for medium preparation, recovery of the salts used in the medium, and a simple cell lysis process with water to harvest the polymer granules [ 7 , 8 ]. Consequently, as bioplastic producers, haloarchaea have advantages over other bacterial strains, hence minimizing the production cost of PHA [ 9 , 10 ]. Consequently, finding new PHA producers within haloarchaea is crucial for cost-effective polymer manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Extremophilic microorganisms, particularly haloarchaea, show all the optimum features to be a good candidate to produce PHA on a large scale: Microbial growth can be achieved by using waste carbon sources and there is no need for medium sterilization, minimal risk of contamination by other microorganisms, use of brines or seawater for medium preparation, recovery of the salts used in the medium, and a simple cell lysis process with water to harvest the polymer granules [ 7 , 8 ]. Consequently, as bioplastic producers, haloarchaea have advantages over other bacterial strains, hence minimizing the production cost of PHA [ 9 , 10 ]. Consequently, finding new PHA producers within haloarchaea is crucial for cost-effective polymer manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…7 Using renewable, low-cost carbon sources, the halophilic archaea, as cell factories, are believed to synthesize PHA, lowering the cost of fermentation in comparison to other extremophiles. 8…”
Section: Introductionmentioning
confidence: 99%
“…7 Using renewable, low-cost carbon sources, the halophilic archaea, as cell factories, are believed to synthesize PHA, lowering the cost of fermentation in comparison to other extremophiles. 8 Several studies have shown that haloarcheon Haloferax mediterranei can utilize a variety of industrial and domestic wastes as carbon sources for making PHA in a very efficient way, e.g., olive oil waste water, crude glycerol phase, starch waste, surplus whey. [9][10][11][12] Also, a lot of research has shown that the PHA produced by Haloferax mediterranei is a mixture of 3-hydroxybutyrate and 3hydroxyvalerate, when different carbon sources were used in the growth medium.…”
Section: Introductionmentioning
confidence: 99%
“…The adequate amount of nitrogen and sulfur has been linked to increased plant growth. Furthermore, the genus Halorubrum is known to produce carotenoids and poly(3-Hydroxybutyrate) with diverse biotechnological applications ( 41 , 42 ). The species Halovenus aranensis and Halovenus carboxidivorans have exhibited the production of carotenoids and carbon monoxide oxidizing capacity ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%